Development of a virtual bench for simulation and monitoring of water heating devices - Oliveira, Jonathan Daniel (2021)
A controller for thermal systems is normally equipped with many facilities to make it flexible and the heating systems more cost-efficient. This results in a number of input parameters to be given by the user. It is not obvious how to choose appropriate values for these parameters unless the user has a large experience in this field. Water heating is a very important part of a household's energy use, and tankless gas water heaters (TGWH) are widely used. There are design and engineering challenges to develop more efficient devices, with lower emissions of pollutant gases and providing comfort improvements from the user point of view. Mathematical and semi-empirical models of the thermal systems were developed in order to simulate the dynamic models of water heating devices. A simulated environment is a less expensive and fastest way of evaluating the relative merits of different control schemes for a given thermal system. A technique to accelerate the process for developing controllers was implemented. Hardware-in-the-loop simulation (HILS) has proved to be very useful to test hardware controllers in virtual environments simulated in real-time. In the scope of the Smart Green Homes Project, a virtual test bench with a TGWH was proposed to support the multiple phases of controller's development, whether it is to control a real or a virtual system. The experimental platform was developed to test the implemented hybrid models performance in hardware-in-the-loop simulation experiences. The platform is composed by a TGWH with a group of sensors, by real-time hardware and by a package of software tools for data acquisition and control. In the final stage of this work, two case studies were carried out, in which the first was dedicated to the validation of the virtual bench concept and the second was to control and monitor a water heating device. Very satisfactory results, from a set of HILS experiences performed in real-time simulations, were obtained for the semi-empirical models proposed.